Obtaining of lead (II) sulfate by polarization of bipolar lead electrodes with alternating current - Bayeshova, A.K.; Kongyratbay, A.M.; Zhumabay, F.M.; Bayeshov, A.; Leska, B. (KSU publ., 2019)
The process of electrolysis using bipolar lead electrodesat polarization by alternating current of industrial frequency (50 Hz) in sulfuric acid solutions was studied for the first time. It is shown that the oxidation of lead to the bivalent state on all monopolar and bipolar electrodes takes place in the anode half-period of alternating current. Next, the anode half-period is replaced by a cathode half-period, then the lead electrode becomes a cathode and hydrogen is released on its surface. Lead (II) ions react with sulfate anions in the near-electrode space to form lead (II) sulfate. It was found that the total loss of electrode mass increases with increasing current density up to 1200–1400 A/m2, and in the region of 2000 A/m2 — significantly decreases, which is associated with increased adverse reactions.In the interval of experiment duration 0.5–2 hours the total loss of electrode mass increases. However, after 2 hoursthis value remains almost constant. Apparently, lead (II) sulfate begins to be accumulating on the electrodes and interfere with the dissolution process. It was found that when using bipolar electrodes, the mass of lead (II) sulfate is about 2.4 times greater at the same current strength than when conducting electrolysis with only two monopolar electrodes.
Keywords: lead; bipolar electrode; electrolysis; alternating current; oxidation; anodic half-period; sulfuric acid